Strength of the shoulder rotators in second-league volleyball players - Popieluch, A.; Staniszewski, M.; Wychowanski, M. (Polish Journal of Sport and Tourism, 2015)
The main aim of the study was to assess the strength of the shoulder rotator muscles of a group of second-league volleyball players. These muscles are assumed to have a crucial impact on attack effectiveness in volleyball. Strength was assessed based on peak torque values obtained for the rotator muscles measured using the maximal voluntary contraction (MVC) method. Torque was measured in both limbs and the differences between the two limbs were examined. The torque values obtained for the volleyball players were also compared against those measured in a group of students who had never trained any sports. Material and methods. The study involved 20 students (mean age = 20 ± 1 years) who played in the second league when the study was conducted. Their results were compared with those of a control group consisting of 30 students (mean age = 20 ± 1 years) who had not trained any sports. Peak torque of the shoulder rotator muscles was measured during external and internal rotation of the shoulder in isometric conditions. The assessment was performed on a special measuring station with the forearm in a vertical and horizontal position. The following basic statistics were calculated for the torque values obtained in the measurement: the mean, standard deviation, minimum value, and maximum value. The data were then subjected to statistical testing. Results. Compared to the students, the volleyball players had higher torque values of the internal and external rotators of the right and left shoulders, in both positions of the forearm. When the results obtained for the right and left limbs were compared for the group of volleyball players, it was found that the torque values for the right limb, which was the dominant limb, were significantly higher than those recorded for the left limb. The study also showed that the position of the forearm had an impact on torque values: when the forearm was in a horizontal position, higher mean values were obtained for the external rotators of the right (p < 0.05) and left (p < 0.01) limbs, and when it was in a vertical one, the internal rotators were stronger compared to the external rotators. Conclusions. The shoulder rotator muscles of the volleyball players were found to be considerably stronger than those of the students, and the rotators of the dominant limb were significantly stronger than those of the non-dominant limb in the group of volleyball players. The position of the forearm had a considerable impact on the strength of the internal and external rotator muscles. The maximal voluntary contraction method used in the study can be helpful in measuring the strength of the shoulder rotator muscles in any phase of the training process.